Controller for the stand alone room lighting powered by wind energy / Mat Nizam Mahmud - Mahmud, Mat Nizam (2010)
Renewable energy sources such as wind energy for electric power supply has received considerable attention in recently due to global environmental concerns associated with conventional generation and potential worldwide energy shortages. This wind energy is free and available everywhere. There are two types of wind energy system which is on-grind system and off-grid system. On g-grid system is for large power generation and off grid system is small power application. Off- grid system also know as standalone wind energy system that used in small application such as in village or house. The primary focus in this project is to design the suitable charge controller for prototype of stand-alone room lighting powered by wind energy. This controller design will involved two main development part which is software development and hardware development. This controller design will provide the protection to the battery during the charging and discharging activities. This is due to battery charger have it limiter for upper and lower voltage. In other way, the indicator Led and charging status display is design to convenience for costumer to checking the status of the system. Apart from that, the controller design also provide the protection from the over speeding of wind turbine that produce over voltage. All those characteristics of controller are design to produce high efficiency controller and compatible with the battery charger design and wind turbine design. Then the controller will integrate with prototype of the stand alone room lighting and test was carried out to test the performance of the prototype in two different room size.